Improvement of thermostability and catalytic efficiency of xylanase from Myceliophthora thermophilar by N-terminal and C-terminal truncation - Yang, Yue; Zhang, Chengnan; Lu, Hongyun; Wu, QiuHua; Wu, Yanfang; Li, Weiwei; Li, Xiuting (Frontiers in Microbiology, 2024)
Mining xylanase from thermophilic filamentous fungi is a feasible way to obtain xylanase with desirable thermal stability. In this study, a glycoside hydrolase (GH) family 11-type xylanase Mtxylan2 was identified through differential expression analysis as well as enrichment analysis based on the transcriptomics data of Myceliophthora thermophilic destructive ATCC42464. The specific enzyme activity of Mtxylan2 was 104.67 U/mg and the optimum temperature of Mtxylan2 was 65 o C. By comparing the sequence of Mtxylan2 with more than ten xylanases, it was found that Mtxylan2 has abnormal sequences at the N-terminal and C-terminal. Three mutants, N-terminal (1M-11Q) truncation mutant 28N, C-terminal (206S-260L) truncation mutant 28C, and N-terminal (1M-11Q) and C-terminal (206S-260L) simultaneous truncation mutant 28NC, were constructed. The catalytic activity of all three mutants was enhanced and the thermal stability of 28C was improved. In particular, 28C showed a 9.3-fold increase in catalytic activity, and the optimum temperature was increased by 5 o C to 70 o C , and the residual enzyme activity remained above 80% after holding at 50-65 o C for 30 min. This study indicated that redundant C-terminal truncations could improve the thermostability and catalytic performance of GH11 xylanase.